Electrically controlled drug release of donepezil and BiFeO3 magnetic nanoparticle-loaded PVA microbubbles/nanoparticles for the treatment of Alzheimer's disease - SAYIN, FATİH SERDAR; ÇAM, MUHAMMET EMİN; GÜNDÜZ, OĞUZHAN (Editions de Sante, 2021)
Nanocarriers are used to deliver bioactive substances in the treatment of neurodegenerative diseases such as Alzheimer's disease (AD). These nanocarriers have shown many benefits over traditional treatments due to their properties such as efficient distribution and controlled release of bioactive material to the brain and loading of various drugs simultaneously. In this study, polyvinyl alcohol (PVA), PVA/bismuth ferrite (BiFeO3), and PVA/BiFeO3/donepezil hydrochloride (DO) monodisperse polymeric nanoparticles were manufactured with bursting microbubbles by a T-junction device. Here, BiFeO3 nanoparticles were synthesized by the co-precipitation method, and these magnetic nanoparticles and DO were loaded in PVA nanoparticles. Nanoparticles had a smooth and monodisperse structure according to SEM images. Also, the diameters of PVA, PVA/BiFeO3, and PVA/BiFeO3/DO nanoparticles were 148 ± 15 nm, 159 ± 21 nm, and 164 ± 12 nm, respectively. It was confirmed by X-ray diffraction and infrared spectroscopy that BiFeO3 magnetic nanoparticles and DO were successfully loaded into nanoparticles produced with PVA. There was no cytotoxic effect on healthy L929 cells for all nanoparticle samples. A systematic electrical circuit has been established to investigate the electrically controlled release behaviour of PVA/BiFeO3/DO nanoparticles at different voltages (0 V, −1.0 V, −0.5 V, +0.5 V, +1.0 V), different currents (−50 μA, −100 μA, −200 μA, and −300 μA), and 200 rpm. To apply electric stimulus increased the release except for +1.0 V and the release of DO increased at more negative voltages with a total release of 68.9% of DO after 15 stimulus with −1.0 V. Higher R2 values were obtained with the Higuchi model for almost all conditions and DO was released from nanoparticles through the non-Fickian diffusion mechanism (0.45 < n < 1). The possibility of affecting the release of DO by modifying the current and voltage in the presence of BiFeO3 leads to an immensely controllable and delicately tunable drug release for AD treatment. © 2021
Keywords: Alzheimer's disease; Bismuth ferrites; Donepezil hydrochloride; Electrically controlled drug release; Microbubble; Nanoparticle